In vivo microcapillary sampling coupled with matrix-assisted laser desorption/ionization fourier transform ion cyclotron resonance mass spectrometry for real-time monitoring of paraquat and diquat in living vegetables. (15th September 2022) - Chen, Chao; Huang, Yan; Wu, Peishan; Pan, Jiachuan; Guo, Pengran; Liu, Shuqin
Highlights: In vivo MCS/MALDI-FTICR-MS method was first developed for detection of herbicides. MALDI-FTICR-MS method required only a very small sample. The tacing assay revealed diquat was more easily absorbed by plants than paraquat. In vivo MCS method can assess herbicide risks for agricultural production. Abstract: An in vivo microcapillary sampling (MCS) method coupled with matrix-assisted laser desorption/ionization fourier transform ion cyclotron resonance mass spectrometry (MALDI-FTICR-MS) analysis was utilized to monitor the real-time bipyridine quaternary ammonium herbicides concentrations and assess their uptake and elimination behaviors in living cabbage plants noninvasively. Under optimized conditions, the proposed method for paraquat (PQ) and diquat (DQ) determination showed wide linear ranges (7.81–500 μg/kg), low limits of detection (0.1–0.9 μg/kg), and good reproducibility. In vivo tracking results demonstrated that different absorption behaviors between PQ and DQ existed in living vegetables and DQ was more easily absorbed. Through decay kinetics model fitting, herbicide half-lives were 1.32 and 1.86 days for PQ and DQ, respectively. To summarize, in vivo MCS method provides valuable information on herbicide risks for agricultural production, which is suitable for temporal, spatial, and longitudinal studies in the same living system and multicompartmental studies in the same organism.